(untitled) (Agricultural Engineering, 2016)
Mechanical and rheological properties of zucchini dried with spouted microwave - assisted heating was analysed. During spouted drying two levels of microwave power were applied: 100W and 250W. Tests were carried out for the raw material blanched in the temperature of 60ºC for 10 minutes and not subjected to a pretreatment. Compression resistance, cutting resistance and stresses relaxation ratios a and b were determined. A significant impact of drying conditions on the product quality within the scope of mechanical and rheological properties was reported. Raw zucchini has 5 to 7 times higher compression resistance, several times lowered cutting resistance and almost two times higher elasticity in comparison to dried material. Low-temperature blanching significantly affected the values of all investigated properties of dried zucchini. Change in microwave powers during spouted drying significantly influenced the increase of the compression work value.